A Comparative Case Study of GED programs at Four Illinois Community Colleges: Perceptions of Effective Instruction - Raiana Mearns (Adult Education Research Conference, 2009)
In this study, the researcher wanted to understand the dynamics of a GED classroom as it related to effective instructional practice. Teachers, students and administrators were asked what they considered to be effective strategies and how those perceptions were shared across groups to build a shared instructional vision.